2010
DOI: 10.1038/ijo.2010.161
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and body-weight development during puberty in a Dutch children cohort

Abstract: Background: Short sleep duration is associated with obesity during childhood and adulthood. Objective: The objective of our study was to investigate the relationship between sleep duration and body mass index (BMI) from Tanner stages 1 to 5 in a Dutch children cohort. Design: In 98 children, anthropometric measurements and leptin concentrations were measured from age 7 to 16 years; body composition, physical activity (Baecke questionnaire), hours television viewing and self-reported sleep duration were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 54 publications
3
30
2
1
Order By: Relevance
“…Four children studies controlled for television viewing and no other media (22, 39, 53, 55) and one study controlled for television and video games (57). Given the recent dramatic increase in use of entertainment media, the early evidence of associations between television with both sleep and obesity, and reports that television comprised only 58% of total media use for youth in the U.S. in 2009 (21), it would seem essential that a broader range of media be routinely included a list of potentially confounding variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four children studies controlled for television viewing and no other media (22, 39, 53, 55) and one study controlled for television and video games (57). Given the recent dramatic increase in use of entertainment media, the early evidence of associations between television with both sleep and obesity, and reports that television comprised only 58% of total media use for youth in the U.S. in 2009 (21), it would seem essential that a broader range of media be routinely included a list of potentially confounding variables.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded two examined articles (37, 38) that used longitudinal analyses to investigate the relationship between sleep duration and weight gain because the measure of sleep duration came at the end of the longitudinal period rather than at the beginning. We excluded another study because it measured the effect of BMI during childhood on sleep duration change (39). …”
Section: Methodsmentioning
confidence: 99%
“…These items, adapted from the Night Eating Questionnaire, were used to compute average hours of night sleeping and napping, and constituted total sleep. Similar sleep questions have been used with this age group in various studies [3;5;11;12]. …”
Section: Methodsmentioning
confidence: 99%
“…(Shi, et al, 2010) Longitudinal studies have resulted in similar findings to these cross-sectional studies. Toddlers and children who slept fewer hours were more likely to be overweight three to six years later (Bell & Zimmerman, 2010;Lumeng, et al, 2007;Marshall et al, 2008) and adolescents whose sleep duration decreased during puberty were more likely to experience an increase in BMI during that same period (Rutters, Gerver, Nieuwenhuizen, Verhoef, & Westerterp-Plantenga, 2010). Another notable study found that short sleep duration in childhood predicted obesity at age 32 (Landhuis, Poulton, Welch, & Hancox, 2008).…”
Section: Sleepmentioning
confidence: 99%